Situational theory of problem solving (STOPS): a foundational theory of publics and it’s application in an eastern cultural context - Xuemei, Chen; Hashim, Norliana; Kamarudin, Syafila (Human Resource Management Academic Research Society, 2024)
In order to adapt to the pace of the development of the times, in 2006, the Situational Theory of Problem Solving (STOPS) was developed based on the Situational Theory of Publics. The concept of the Situational Theory of Publics is expanded by the Situational Theory of Problem Solving (STOPS), especially the concept of the dependent variable of communicative action (Kim, 2006; Kim & Ni, 2013). The situational theory of problem solving (STOPS) has deeply developed the perspective and characteristics of public problem recognition and explained people's communication behavior based on different situations (Kim, 2006). It describes the methods people employ to solve problems cognitively and through communication. It is also feasible to distinguish publics based on their cognitive philosophies and communication behaviors, which allows for a more thorough segmentation of publics (Ni & Kim, 2009). According to Kim and Grunig (2011), developed the comprehensive of Situational Theory of Publics (STP) between problem solving and communication. STOPS directs the strategic development of public relations practice through an understanding of the factors that drive individuals to communicate in favor of or against organizations. However, STOPS is a communication theory developed within the context of Western culture. The application of STOPS in an Eastern cultural context should consider the role of Antecedent Factors. These antecedent variables are included to increase the theory’s capacity to explain certain issues. This study focus on discuss the Situational Theory of Problem Solving (STOPS)，and the application in an Eastern cultural context.